Jawabanmu

2014-01-14T13:54:14+07:00
Y = 2x - 5                                                                                                                          3y - 9x + 6 = 0                                                                                                                     3 ( 2x - 5 ) - 9x + 6 = 0                                                                                               6x - 15 - 9x + 6 = 0                                                                                                          6x - 9x - 15 + 6 = 0                                                                                                              -3x = 15 - 6                                                                                                               -3x = 9                                                                                                                           x = -3

mencari y nya gmn?
oh ya maaf ketinggalan, 3y - 9x + 6 = 0 kemudian 3y - 9 ( -3) + 6 = 0 kemudian 3y + 27 + 6 = 0 kemudian 3y = -27 - 6 kemudian 3y = -33 kemudian y = -11
ini kemasuk metode gabungan bukan?
metode subtitusi